Causes and consequences of plasticity in parental and offspring behaviour in the burying beetle Nicrophorus vespilloides - Ratz, Tom (The University of Edinburgh, 2021)
Behavioural plasticity, the environmentally induced change in behaviour, is a reversible response that allows a rapid switch in activity to best match the environment. Behavioural plasticity is a widespread mechanism influencing the ability to find resources, reproduce and survive. Behavioural plasticity is particularly important in parent-offspring interactions because it allows parents and offspring to finely tune costly behaviours, such as parental care or offspring begging, to avoid unnecessary expenditure and obtain the highest returns from the interaction. In this thesis, I examined the role of plasticity in parental and offspring behaviour in response to changes in various aspects of in the intrinsic and environmental conditions in the burying beetle Nicrophorus vespilloides: energetic costs, infection status, resources availability, and parent’s body size. I first showed how females unexpectedly increase parental care with higher energetic costs and that females do so irrespectively of variation in brood size. Next, I showed that infected females maintain their level of care despite suffering from high mortality. I further showed that resource availability has a positive effect on biparental cooperation over care, as males tend to provide care for longer when resources are more abundant. I also showed how larvae preferentially beg towards larger females as they spend more time associating with larger females over smaller ones. I focused the final part of the thesis on the consequences of behavioural plasticity and tested whether inbreeding can alter plasticity in adult and larval behaviour, and how parent-offspring and male-female interactions mediate the effects of inbreeding depression. I found evidence that inbreeding can increase plasticity in offspring behaviour. Moreover, I found that maternal inbreeding has detrimental effects on offspring survival, and that these effects remain regardless of the presence or the inbreeding status of the male parent. Collectively, these findings confirm that behavioural responses oftentimes allow balancing the costs and benefits of a behaviour, but that the direction of behavioural adjustments can also change unexpectedly depending on prospects for survival and future reproduction. These findings provide further evidence indicating that the intrinsic and environmental conditions not only shape the behavioural responses and fitness of focal individual, but also influence the behavioural responses and fitness of social partners. Overall, these studies provide additional support to the idea that behavioural plasticity might be a key step in the emergence of complex behavioural phenotypes and a major source of behavioural diversity
Keywords: Nicrophorus vespilloides; larvae feeding; regurgitated carrion; environmental behavioural adjustments; energy expenditure; food abundance; adult body size; behavioural plasticity